2021
DOI: 10.1016/j.clinph.2020.12.021
|View full text |Cite
|
Sign up to set email alerts
|

A computational biomarker of juvenile myoclonic epilepsy from resting-state MEG

Abstract: Highlights Computational modelling is combined with MEG to differentiate people with juvenile myoclonic epilepsy from healthy controls. Brain network ictogenicity (BNI) was found higher in people with juvenile myoclonic epilepsy relative to healthy controls. BNI’s classification accuracy in our cohort was 73%.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…We used resting-state MEG functional networks from people with JME and healthy controls. This MEG dataset was previously used to demonstrate that the BNI framework was capable of differentiating the two groups of individuals [31]. In that study, Lopes et al [31] used the theta model with additive coupling (see the Supplementary Material for a description about the theta model), and showed that individuals with epilepsy had higher BNI than controls as hypothesized.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used resting-state MEG functional networks from people with JME and healthy controls. This MEG dataset was previously used to demonstrate that the BNI framework was capable of differentiating the two groups of individuals [31]. In that study, Lopes et al [31] used the theta model with additive coupling (see the Supplementary Material for a description about the theta model), and showed that individuals with epilepsy had higher BNI than controls as hypothesized.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain MEG functional networks, the source reconstructed data were divided into 10, non-overlapping, 20 s segments. A functional network was computed from each segment using a surrogate-corrected amplitude envelope correlation (AEC) with orthogonalised signals [31, 33]. Thus, we considered 10 MEG functional networks per individual.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations